PUSH-PULL CURRENT-TO-CURRENT AND VOLTAGE-TO-CURRENT CONVERTERS WITH OUTPUT SIGNAL SWITCHING - Azarov, Oleksiy; Katsyv, Samoil; Obertyukh, Maksym (Scientific Works of Vinnytsia National Technical University, 2018)
The paper considers push-pull current-to-current and voltage-to-current converters with output signal switching. Relevance and expediency of designing such converters in order to expand functional capabilities due to providing additional ability to perform high-precision fast switching of the signals are substantiated. The circuits of push-pull current-to-current and voltage-to-current converters with output signal switching are proposed and analyzed. In order to analyze dynamic errors, occurring in the process of the diode commutation, its mathematical model is developed and calculated. The modeling results confirm adequacy of the model. Engineering recommendations on circuit implementation of the above push-pull current-to-current and voltage-to-current converters with output signal switching are presented.